Structural basis of urate transport by glucose transporter 9 - Daiki Matsushita; Yu Toyoda; Yongchan Lee; Maeda Aoi; Hirotaka Matsuo; Tappei Takada; Tomohiro Nishizawa (Cell Reports)
Summary: Glucose transporter 9 (GLUT9) is a critical urate transporter involved in renal reabsorption, playing a pivotal role in regulating physiological urate levels and representing a potential therapeutic target for gout. Despite such clinical significance, the structural basis of urate recognition and transport by GLUT9 remains elusive. Here, we present the cryoelectron microscopy (cryo-EM) structures of GLUT9 in the inward-open conformation in both apo and urate-bound states. Urate binds in a cleft between the N-terminal and C-terminal domains, interacting via hydrogen bonds and hydrophobic interactions. Structural comparison with sugar-transporting GLUTs highlights unique amino acid compositions in the substrate recognition pocket of GLUT9. Functional and mutational studies directly measuring GLUT9-mediated urate uptake further demonstrate the cooperative roles of multiple residues in urate recognition. Our findings elucidate the structural basis of urate transport by GLUT9 and provide valuable insights for the development of uricosuric drugs targeting GLUT9.